2007
DOI: 10.5713/ajas.2007.1874
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FSP (Fermented Soy Protein) to Replace Soybean Meal in Weaned Pigs: Growth Performance, Blood Urea Nitrogen and Total Protein Concentrations in Serum and Nutrient Digestibility

Abstract: A total of one hundred and forty four weaned pigs with an average BW of 8.09±0.05 kg were used in a 28 day study to investigate the effects of fermented soy protein on growth performance, blood urea nitrogen and total protein concentrations in serum and nutrient digestibility in weaner pigs. Pigs were blocked by initial body weight and randomly allocated to one of four dietary treatments in a randomized complete block design. There were six replications per treatment. Dietary treatments included: SBM (cornsoyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 17 publications
(19 reference statements)
5
40
0
Order By: Relevance
“…Moreover, several studies have shown that the animals fed high-quality protein feed (i.e. FM-based diet versus soy concentrate-based diet and fermented soy protein diet versus SBM diet) had higher blood concentrations of TP and/or lower BUN levels (Takagi et al 2001;Cho et al 2007). These results indicated a relationship between dietary protein quality and protein metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, several studies have shown that the animals fed high-quality protein feed (i.e. FM-based diet versus soy concentrate-based diet and fermented soy protein diet versus SBM diet) had higher blood concentrations of TP and/or lower BUN levels (Takagi et al 2001;Cho et al 2007). These results indicated a relationship between dietary protein quality and protein metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Although the ingredients was different, Vranjes and Wenk (1995) reported that barley fermented by enzyme had a more impact on chick performance than unfermented barley form. Cho et al (2007) reported that piglets fed fermented soya beans showed increased feed efficiency. The study of Kim et al (2010) also documented that during nursery pigs at 3 to 7 wk of age, a significant increase of ADG and ADFI were observed in treatments fed fermented soybean meal.…”
Section: Discussionmentioning
confidence: 99%
“…To remove the antinutritional factors and improve biological values of soyabean meal (SBM), many species of microbes such as lactic acid bacteria (Cho et al, 2007) and Bacillus subtilis (Kiers et al, 2003) have been used for fermenting SBM. This result indicated that SBM fermented with the optimal microbial proportions could reduce antigen protein by enzymatic hydrolysis and microbial fermentation as well as increase protein, lactic acid, probiotics, acid-soluble protein, total and most amino acid contents in fermented soyabean meal (FSBM), which is in agreement with previous reports (Hachmeister and Fung, 1993;Zhao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%